The Effects of Different Roasting Degrees on Antioxidant of Coffee From West Sumatra - Muhammad Isa Dwijatmoko; R. A. Fadri; S. Syahrul; M. Harni; Y. Muchrida (University of Sultan Ageng Tirtayasa, 2024)
Coffee has several benefits for human health because it contains bioactive components and one of which is polyphenol components. Regional differences in coffee cultivation and roasting processes influence the polyphenol content. The aim of this research was to explain the effect of roasting temperature and the area of region of coffee. Coffee beans were obtained from three regions, which are Solok, Situjuh and Pasaman, West Sumatra. Coffee beans were roasted with three temperatures, 191-200oC (light), 201-210oC (medium), and 211-220oC (dark) for ±20 min, and other factors were considered as constant. Next, the coffee beans were analyzed for air content, color, flavonoids, total phenols and antioxidant activity. Results of the research analysis used SPSS. The results of the research showed that during the roasting process, coffee beans experienced a decrease in the attributes of color, water content, total phenols, total flavonoids and antioxidant activity. Overall, coffee beans at the light roast level had high attribute values of color, water content, total phenols, total flavonoids and antioxidant activity, whereas the highest in Solok coffee bean samples were antioxidant activity 27.45 ± 13.37 % and flavonoids 6.93 ± 0.33 mgEQ/g, the highest in Situjuh were total phenols 85.57 ± 3.84 mg GAE/ g and water content 3.17 ± 0.21 %, and the highest in Pasaman was color 24.49 ± 1.32 (L). Meanwhile, coffee beans at the dark roasting level had low attribute values of color, water content, total phenols, total flavonoids and antioxidant activity, whereas the lowest in Solok coffee bean samples were water content 1.44 ± 0.48 % and color 16.08 ± 0.19 (L), the lowest in Situjuh were antioxidant activity 14.82 ± 1.15 % and total flavonoids 4.47 ± 0.36 mgEQ/g, and the lowest in Pasaman was total phenol 50.35 ± 4.63 mg GAE/ g.